Social capital and economic development: The case of Uzbekistan - Manuela Troschke (Osteuropa-Institut Regensburg, 2011)
While most transition countries suffered substantially from the world financial crisis of 2008 and still cope with its consequences, Uzbekistan has stayed almost untouched and shows constant economic growth since 2001. Neither macroeconomic foundations nor available institutional indicators provide an explanation for the sustained Uzbek Growth Puzzle (Zettelmeyer, 1999). This paper argues that social capital plays a major role in this puzzle. I examine how social capital has contributed to (1) the ease of transition, (2) the development of effective markets and (3) the development of an effective government. In view of the empirical results from other countries, I analyze the Uzbek case with the help of stylized facts for Uzbek social capital and the data derived from the AsiaBarometer surveys for 2003 and 2005.
Keywords: 330; Wirtschaftswachstum; Entwicklung; Übergangswirtschaft; Social Capital; Usbekistan